An oligoclonal antibody durably overcomes resistance of lung cancer to third‐generation EGFR inhibitors. Issue 2 (6th December 2017) - Mancini, Maicol; Gal, Hilah; Gaborit, Nadège; Mazzeo, Luigi; Romaniello, Donatella; Salame, Tomer Meir; Lindzen, Moshit; Mahlknecht, Georg; Enuka, Yehoshua; Burton, Dominick GA; Roth, Lee; Noronha, Ashish; et al.
Abstract: Epidermal growth factor receptor ( EGFR ) mutations identify patients with lung cancer who derive benefit from kinase inhibitors. However, most patients eventually develop resistance, primarily due to the T790M second‐site mutation. Irreversible inhibitors (e.g., osimertinib/AZD9291) inhibit T790M‐EGFR, but several mechanisms, including a third‐site mutation, C797S, confer renewed resistance. We previously reported that a triple mixture of monoclonal antibodies, 3×mAbs, simultaneously targeting EGFR, HER2, and HER3, inhibits T790M‐expressing tumors. We now report that 3×mAbs, including a triplet containing cetuximab and trastuzumab, inhibits C797S‐expressing tumors. Unlike osimertinib, which induces apoptosis, 3×mAbs promotes degradation of the three receptors and induces cellular senescence. Consistent with distinct mechanisms, treatments combining 3×mAbs plus sub‐inhibitory doses of osimertinib synergistically and persistently eliminated tumors. Thus, oligoclonal antibodies, either alone or in combination with kinase inhibitors, might preempt repeated cycles of treatment and rapid emergence of resistance. Synopsis: EGFR kinase blockers effectively inhibit a fraction of lung tumors, but second and third site EGFR mutations drive relapses. Acquired resistance to the blockers can be delayed or prevented in animal models by a mixture of three antibodies targeting EGFR/HER1, HER2 and HER3. A mixture containing the clinically approved cetuximab and trastuzumab, in combination with an anti‐HER3 antibody, overcomes resistance to first‐generation EGFR inhibitors. Unlike third‐generation inhibitors (e.g., osimertinib), which cause cell death, the mixture of antibodies accelerates receptor endocytosis and arrests tumor cell growth. The mixture of three antibodies overcomes C797S, an osimertinib‐resistant mutation, and synergizes with osimertinib. Abstract : EGFR kinase blockers effectively inhibit a fraction of lung tumors, but second and third site EGFR mutations drive relapses. Acquired resistance to the blockers can be delayed or prevented in animal models by a mixture of three antibodies targeting EGFR/HER1, HER2 and HER3.